2021
DOI: 10.1111/febs.16291
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring UBIAD1 mutations differentially affect menaquinone biosynthesis and vitamin K‐dependent carboxylation

Abstract: UbiA prenyltransferase domain‐containing protein‐1 (UBIAD1) is responsible for the biosynthesis of menaquinone‐4 (MK‐4), a cofactor for extrahepatic carboxylation of vitamin K‐dependent (VKD) proteins. Genetic variations of UBIAD1 are mainly associated with Schnyder corneal dystrophy (SCD), a disease characterized by abnormal accumulation of cholesterol in the cornea. Results from in vitro studies demonstrate that SCD‐associated UBIAD1 mutations are defective in MK‐4 biosynthesis. However, SCD patients do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
1
0
1
Order By: Relevance
“…Lending support to these findings and possibly supplying corroboratory data, Chen et al [158], report a HEK293 cell-based model in which they selectively insert and test UBIAD1 mutant variants and independently measure MK4 biosynthesis and VKD protein carboxylation. Comparing p.Asn112Asp to p.Asp102Ser variants, they found an approximate 4.7x difference in VKD carboxylation which is in line with the nearly 4x MGP mRNA induction differences produced by these variants found by Sarosiak et al, thus showing some proportionality in the observed variant effects.…”
Section: Schnyder Corneal Dystrophymentioning
confidence: 80%
“…Lending support to these findings and possibly supplying corroboratory data, Chen et al [158], report a HEK293 cell-based model in which they selectively insert and test UBIAD1 mutant variants and independently measure MK4 biosynthesis and VKD protein carboxylation. Comparing p.Asn112Asp to p.Asp102Ser variants, they found an approximate 4.7x difference in VKD carboxylation which is in line with the nearly 4x MGP mRNA induction differences produced by these variants found by Sarosiak et al, thus showing some proportionality in the observed variant effects.…”
Section: Schnyder Corneal Dystrophymentioning
confidence: 80%
“…Кроме того, было показано, что концентрация МК-4 в головном мозге крысы положительно коррелирует с концентрацией сфинголипидов, особенно с сульфатидами и сфингомиелином, и как К1, так и МК-4 увеличиваются с потреблением К1. Это согласуется с представлением о том, что МК-4 является результатом конверсии К1 и что церебральный МК-4 возникает в результате приема К1 [34]. Несколько исследований на людях продемонстрировали наличие взаимосвязи между низким уровнем K1 и риском развития болезни Альцгеймера и ухудшением памяти у пожилых людей [26,35].…”
Section: обзорыunclassified
“…No further information regarding UBIAD1 is published to date. However, taking into account these previous studies on SCD 69,131,135,136 , we hypothesise that there is a permanent or incorrect binding between HMGCR and UBIAD1, probably caused by the PTM in HMGCR under CKD conditions, that affects and decreases vitamin K2 synthesis. More studies on HMGCR-UBIAD1 binding and vitamin K status would be needed.…”
Section: Discussionmentioning
confidence: 84%
“…However, to date, there are not enough data available about this dystrophy and the vitamin K status of the patients. Nevertheless, in vitro studies have observed that most of the UBIAD1 mutations, associated with SCD, have a minimal effect on both MK4 biosynthesis and carboxylation of vitamin K-dependent proteins, finding only one mutation directly related to MK4 deficiency 135 . Another study in SCD patients has found increased plasma levels of dp-ucMGP, which would also correlate with low vitamin K status 136 .…”
Section: Discussionmentioning
confidence: 99%